2022
DOI: 10.3390/children9111673
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Training Time on Understanding the Treatment of Adolescent Idiopathic Scoliosis According to SOSORT International Guidelines: An Online Survey Study

Abstract: The lack of knowledge by health professionals in the management of scoliosis can lead to an erroneous diagnosis. The aim of the current study was to understand the influence of length of professional experience on the knowledge of Brazilian physical therapists regarding international guidelines for the treatment of adolescent idiopathic scoliosis. The study was conducted using an online questionnaire consisting of 23 questions, divided into 8 questions on sociodemographic data and 15 questions based on informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…A good level of knowledge of IS was only seen among Malaysian physiotherapists with more than five years of clinical experience. Similarly, a study performed on Brazilian physical therapists who have experience for more than six years demonstrated greater knowledge of IS (Linhares et al, 2022). This could be attributed to attending more professional courses and training.…”
Section: Association Between Years Of Clinical Experience and Level O...mentioning
confidence: 90%
See 1 more Smart Citation
“…A good level of knowledge of IS was only seen among Malaysian physiotherapists with more than five years of clinical experience. Similarly, a study performed on Brazilian physical therapists who have experience for more than six years demonstrated greater knowledge of IS (Linhares et al, 2022). This could be attributed to attending more professional courses and training.…”
Section: Association Between Years Of Clinical Experience and Level O...mentioning
confidence: 90%
“…At this point, most Malaysian physiotherapists have poor level of knowledge. Moreover, a recent study's findings indicated that physical therapists with less than six years of clinical training lack understanding of best practice in treating patients with IS (Linhares et al, 2022). A good level of knowledge of IS was only seen among Malaysian physiotherapists with more than five years of clinical experience.…”
Section: Association Between Years Of Clinical Experience and Level O...mentioning
confidence: 99%
“…Most participants of this study had some unpleasant interactions with health professionals, along with the concern that they are not equipped with essential skills and knowledge of scoliosis. A study found that 79% of 1,352 health professionals from 56 countries reported that they do not have enough opportunities for professional development regarding health conditions such as scoliosis and low back pain (Linhares et al, 2022). They believe that the lack of knowledge has negative impact on diagnosing patients and providing proper treatment (Linhares et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A study found that 79% of 1,352 health professionals from 56 countries reported that they do not have enough opportunities for professional development regarding health conditions such as scoliosis and low back pain (Linhares et al, 2022). They believe that the lack of knowledge has negative impact on diagnosing patients and providing proper treatment (Linhares et al, 2022). As people with moderate and severe scoliosis tend to have ongoing interactions with health professionals, this is an area that could be addressed and improved.…”
Section: Discussionmentioning
confidence: 99%